Spaces of Socialization and Behavior change in Hygiene in Lima; 2008 - Meneses Rivas, Max Teodoro (2010)
This article aims to study the areas of socialization and behavior change in hygiene in the popular sectors of metropolitan Lima in 2008. The research presents first to the social actors involved in socialization of hygiene practices. Second, it examines the cultural expressions that use the most popular sectors. Third interprets the main messages highlighted in the socialization spaces. Fourth describes the impacts produced by socialization spaces in relation to water and sanitation. Finally, it presents the conclusions and the relevant literature